KEPENTINGAN APPLE INC DALAM PERDAGANGAN PASAR SELULER DI INDONESIA TAHUN 2011-2015 - Syafira Yunita Annisa; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research describes the interest of apple inc in cellular markets trading in Indonesia on 2011-2015. Many smartphones in the market cellular in Indonesia has resulted in competition between the company smartphone in selling their products. Apple entering Indonesia in 2009 and make sale their products that experienced an increase in from year to year. At the moment apple occupying the position of two for the sale of their products in the position of first occupied by Samsung. The method that is used in this research is qualitative research. Some of the data are obtained from books, journal, articles, internet, and another media. The focus of this research is what the significance apple inc trade cellular market in Indonesia. This research using neoliberalism perspective, the theory competitive advantage from Michael E. Porter and the level analysis group. The interest of apple inc trade cellular market in Indonesia because Indonesia has great potential for the trade. Increasing the sale of products apple over the years, many consumers who use the iPhone, and apple investing in Indonesia by opening the online store. the Indonesian government giving the rules on imports smartphone to Indonesia by imposing import tax smartphone. The regulation TKDN (the component in public) for Apple. And the support of the united states against apple country of origin the company.Key words : Apple Inc, Neoliberalism, Competitive Advantage.